Apoptin Regulates Apoptosis and Autophagy by Modulating Reactive Oxygen Species (ROS) Levels in Human Liver Cancer Cells - Li, Yiquan; Zhu, Yilong; Fang, Jinbo; Li, Wenjie; Li, Shanzhi; Liu, Xing; Liu, Zirui; Song, Gaojie; Shang, Chao; Cong, Jianan; Bai, Bing; Sun, Lili; et al. (Frontiers in Oncology, 2020)
Apoptin is a protein that specifically induces apoptosis in tumor cells. The anti-tumorigenic functions of Apoptin, including autophagy activation and its interaction with apoptosis, have not been precisely elucidated. Here we investigate the main pathways of apoptin-mediated killing of human liver cancer cells, as well as its putative role in autophagy and apoptosis. The anti-proliferative effect of apoptin in liver cancer cells was analyzed in vitro by crystal violet staining and MTS detection, and also in vivo using a tumor-based model. The main pathway related to apoptin-induced growth inhibition in vitro was evaluated by flow cytometry and fluorescence staining. The relationship between apoptosis and autophagy on apoptin-treating cells was analyzed using apoptosis and autophagy inhibitors, mitochondrial staining, Annexin V-FITC/PI flow detection, LC3 staining and western blotting. The effect of ROS towards the apoptosis and autophagy of apoptin-treating cells was also evaluated by ROS detection, Annexin V-FITC/PI flow detection, LC3 staining and western blotting. Inhibition of apoptosis in apoptin-treating liver cancer cells significantly reduced the autophagy levels in vitro. The overall inhibition increased from 12 hrs and the effect was most obvious at 48 h. Inhibition of autophagy could increase apoptin-induced apoptosis of cells in a time-dependent manner, reaching its peak at 24hrs. Apoptin significantly alters ROS levels in liver cancer cells, and this effect is directly related to apoptosis and autophagy. ROS appears to be the key factor linking apoptin-induced autophagy and apoptosis through the mitochondria in liver cancer cells. Therefore, evaluating the interaction between apoptin-induced apoptosis and autophagy is a promising step for the development of alternate tumor therapies.